SOME RESULTS OF PHENOLOGICAL OBSERVATIONS OVER THE MAIN NECTARIFEROUS-POLLINIFEROUS PLANTS OF THE CHUVASH REPUBLIC - A. I. Skvortsov; V. G. Semenov; V. N. Sattarov; D. A. Baimukanov; D. A. Doshanov; G. A. Abdullayeva; L. A. Faizullayeva (Scientific Journal of Pedagogy and Economics, 2020)
It has been proven that favorable prerequisites for the development of bee colonies and the production of high honey flow are created in cases when the apiary is fully surrounded by nectariferous lands (landscapes): forests, meadows, gardens, fields and forest belts with biodiversity of nectar-pollen flora, i.e. a continuous honey flow appears or a flower-nectar conveyor is created. During the phenological observations, beekeepers assured themselves that in order to clearly and fully utilize the nectar-pollen flora, it is necessary to have information from many years of research on the progression of the flowering of the presented plants, starting from early spring and ending in the fall at the end of the beekeeping season. Accurately compiled data of perennial phenological records and a calendar of flowering of entomophilous plants guarantee the beekeeper's opportunities to more rationally control their actions in doing the beekeeping business and improving the honey flow by including newly introduced plants in the flower conveyor that more completely fill the non-honey flow periods. It is safe to hope that, based on the analysis of regular perennial phenological records, each apiary beekeeper can predict the honey flow and make an adjustment to the technology of keeping and caring for the bee colonies. The beekeepers of the apiary of OOO Pchelovodcheskoe of the Kravsnoarmeysky district of the Chuvash Republic have become convinced that by knowing the beginning and end of the full flowering of nectariferouspolliniferous plants, its duration can be determined. Depending on the strength of the honey flow, there are: a no honey flow period, when the bee colony on the control weights shows a decrease in the total mass; supporting honey flow, when the scales show from 0 to 0.6 kg of profit, while the honey in bee colonies does not increase in the direction of profit and does not accumulate in an amount sufficient for pumping the marketable honey; productive honey flow, when reference scales show from 1 kg or more of nectar profit per day. In this case, the amount of ripe honey in colonies will be sufficient for selection and pumping. It should be noted that the main honey flow is the strongest productive honey flow when from each main wintering colony, full unopened honeycomb frames from several honey chambers or shells are pumped out, which is the eventual result of the economic efficiency of the apiary. Analysis of the results of phenological observations allows us to note the shift of the period of the beginning and the end of flowering in other plant species. It should be noted that in both 2017 and 2018, the species composition of the flora in the investigated area has blossomed continuously, ending in August and September: in European goldenrod (Solidago virgaurea) - 01/09/2017 and 28/08/2018; in common globe thistle (Echinops sphaerocephalus) - 09/05/2017 and 08/20/2018.